BUSINESS COMMUNICATION OF UMKM - Ichsan Adil Prayogi (Bussman Journal : Indonesian Journal of Business and Management, 2021)
This research is motivated to find out what and how business communication is carried out by SMEs Onion sticks from Mancak Village. By using qualitative research methods and a case study approach, by making Fatimah who is the founder of this MSME, and Febby Fitriani the owner, both of which are resource persons in this research, the authors found that MSME Sticks in Mancak Village initially only used interpersonal communication. by entrusting their products to the surrounding stalls. After two years since it was founded in 2015, it was only in 2022 that this Stick MSME began rejuvenation with new packaging which had a positive impact on increasing product sales. In 2022, UKMS Onion Sticks will start selling via e-commerce Shopee, but the complexity of e-commerce tools and the need for the latest or additional gadgets, therefore marketing through e-commerce has not run optimally. The SWOT analysis is also attached at the end of the discussion to provide positive input for the MSME Sticks of Mancak Village in particular, and MSMEs for food products in general